Mechanisms underlying purinergic P2X3 receptor-mediated mechanical allodynia induced in diabetic rats - Xu Guang-Yin; Li Guangwen; Liu Ningang; Huang Li-Yen (SAGE Publishing, 2011)
Abstract Background Diabetic neuropathy is a common neuropathy associated with paresthaesia and pain. The mechanisms underlying the painful conditions are not well understood. The aim of this study is to investigate the participation of purinergic P2X3 receptors in painful diabetic neuropathy. Results Diabetes was induced by an intraperitoneal injection of streptozotocin (STZ). We showed that mechanical allodynia was induced two weeks after a STZ injection and lasted for at least another seven weeks. The mechanical allodynia was significantly attenuated by peripheral administration of the P2X receptor antagonists, PPADS or TNP-ATP. DiI was subcutaneously injected into the rat hindpaw to label hindpaw-innervated dorsal root ganglion (DRG) neurons. ATP activated fast-inactivating P2X3 receptor-mediated currents in the labeled DRG neurons were studied. ATP responses in STZ-treated rats were ~2-fold larger than those in control rats. Furthermore, the expression of P2X3 receptor proteins in the plasma membrane of L4-6 DRGs of STZ rats was significantly enhanced while the total expression of P2X3 receptors remained unaltered. Conclusions These results indicate that a large enhancement of P2X3 receptor activity and an increase in the membrane expression of P2X3 receptors contribute to the development of chronic pain in STZ-induced diabetic rats and suggest a possible target for the treatment of diabetic neuropathic pain.